Educational competencies of male and female teachers of physical education in, Northwestern Badia Directorate of Education - Albarri, Habis Ghazi (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the educational competencies of male and female teachers of physical education in the northwestern Badia. The study sample consisted of (87) male and female teachers. The researcher used the descriptive approach to its suitability for the study. For educational competencies, the results showed that the degree of male and female teachers’ acquisition of educational competencies was medium with an average of (3.22), according to the following order: implementation competencies with an average of (3.38), teaching strategies competencies with an average of (3.27), evaluation competencies with an average of (3.24), Planning arithmetic mean suspicious deaths (3.12). The results also showed statistically significant differences (α = 0.05) between the arithmetic averages from the point of view of male and female teachers due to the variable of years of experience and for the benefit of the longest experience, and in light of the results the researcher recommended a set of recommendations, most notably: Holding training courses for teachers that would be interested in preparing them In practice, they possess the necessary skills to teach physical education curricula.